2010
DOI: 10.1159/000314675
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Candidal Carriage with Dental Caries in Children

Abstract: Introduction: Oral candidiasis is one of the most common opportunistic oral fungal infections. Oral candidal carriage in schoolchildren is a subject of increasing interest worldwide and has recently been associated with increased caries incidence in children. Aims: This study was carried out to identify association between oral candidal carriage in children and dental caries. Subjects and Methods: One hundred subjects with an age range between 6 and 12 years were included in this study. The subjects were distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
149
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(163 citation statements)
references
References 27 publications
9
149
0
5
Order By: Relevance
“…An organism of interest in this context is C. albicans, a yeast frequently isolated from patients with caries. Studies have identified a higher incidence rate of C. albicans in children with caries compared to caries-free children [51,52]. A recent systematic review by Xiao and co-workers (2018) indeed confirmed this co-isolation, stating that children with oral C. albicans colonisation, can be > 5 times more likely to develop early childhood caries (ECC) [53•].…”
Section: Caries: Slimy Residentsmentioning
confidence: 99%
“…An organism of interest in this context is C. albicans, a yeast frequently isolated from patients with caries. Studies have identified a higher incidence rate of C. albicans in children with caries compared to caries-free children [51,52]. A recent systematic review by Xiao and co-workers (2018) indeed confirmed this co-isolation, stating that children with oral C. albicans colonisation, can be > 5 times more likely to develop early childhood caries (ECC) [53•].…”
Section: Caries: Slimy Residentsmentioning
confidence: 99%
“…albicans and S. mutans are found together in early childhood caries (Marchant et al, 2001;de Carvalho et al, 2006;Raja et al, 2010) and on bracket materials (Rammohan et al, 2012). Early childhood caries is a very aggressive form of caries.…”
Section: Introductionmentioning
confidence: 99%
“…Early childhood caries is a very aggressive form of caries. It has been shown that C, albicans is present in 96% of caries-positive children (age group 6-12 years) but only in 24% of caries-free children (Raja et al, 2010). Denture plaque was shown to contain both S. mutans and C. albicans in 25.5% of healthy individuals (Ribeiro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[1] [2]. Candida albicans is one of the most important opportunistic fungal pathogens responsible for superficial mucocutaneous infections of non-genital (Oropharyngeal) and genital (VVC, balanitis and balanoposthitis and candiduria) tracts of healthy individuals to life threatening, invasive infections in immunocompromised patients [1]- [3].…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans is one of the most important opportunistic fungal pathogens responsible for superficial mucocutaneous infections of non-genital (Oropharyngeal) and genital (VVC, balanitis and balanoposthitis and candiduria) tracts of healthy individuals to life threatening, invasive infections in immunocompromised patients [1]- [3]. Oral candidiasis may be of pseudomembranous, hyperplastic, erythematous, angular cheilitis and Denture stomatitis type [2] [3]. It was also reported to be associated with caries in children and dental loss [1]- [3].…”
Section: Introductionmentioning
confidence: 99%